Halophytes and Climate Change: Adaptive Mechanisms and Potential Uses 2019
DOI: 10.1079/9781786394330.0324
|View full text |Cite
|
Sign up to set email alerts
|

Practical uses of halophytic plants as sources of food and fodder.

Abstract: Halophytes are plants that are adapted to saline soils in their natural habitats because they are salt tolerant. They are found in a range of environments with varied salinity and climatic conditions. These plant species can be irrigated with saline water and cultivated on saline soils that are unsuitable for commercial crops. Halophytes are rich in nutrients, such as antioxidants, fatty acids and amino acids, and many species have been used traditionally as herbs and vegetables, feed and fodder. Therefore, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…From all the above referred it is easy to deduce that halophyte plants may find niches in the demanding market for novelties, as for example as herbs, vegetables, fresh gourmet products, and animal feed. One challenge that limits halophyte cultivation is the lack of knowledge about consumers' acceptance of halophyte products, which are fundamental to the commercialization of halophytes because farmers will start investing in the crop only if there is marketing potential (Centofanti and Banuelos, 2019). Halophytes are non-conventional crops and it would take a little to make people believe that they are good food for them, although some are used by certain communities for this purpose (Menzel and Leith, 1999).…”
Section: Economic Applications Of Halophytes and Potential Marketsmentioning
confidence: 99%
“…From all the above referred it is easy to deduce that halophyte plants may find niches in the demanding market for novelties, as for example as herbs, vegetables, fresh gourmet products, and animal feed. One challenge that limits halophyte cultivation is the lack of knowledge about consumers' acceptance of halophyte products, which are fundamental to the commercialization of halophytes because farmers will start investing in the crop only if there is marketing potential (Centofanti and Banuelos, 2019). Halophytes are non-conventional crops and it would take a little to make people believe that they are good food for them, although some are used by certain communities for this purpose (Menzel and Leith, 1999).…”
Section: Economic Applications Of Halophytes and Potential Marketsmentioning
confidence: 99%
“…Among other properties, it has been found that Salicornia members have a high content of polyunsaturated fatty acids (PUFAs) and polyphenols, which are beneficial for human consumption because of their antioxidant properties [ 7 , 9 ]. In halophytes, it is known that these molecules are accumulated to higher concentrations in unstressed conditions, as compared to glycophytes, to cope with salinity-induced oxidative stress [ 11 ]. In S. ramosissima , the most abundant PUFAs are linolenic acid (omega-3) and linoleic acid (omega-6), which are essential FAs for humans because the human body is not able to synthesize them [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of halophytes under greenhouse conditions-either in soil or in a soil-less system-or in an open field, to produce raw or minimally processed vegetables Horticulturae 2022, 8, 195 2 of 32 (i.e., ready-to-eat or fresh-cut products), in particular for gourmet cuisine, is of growing interest [7][8][9]. The edible parts of these species are appreciated due to their salty taste and high content in antioxidant compounds and essential nutrients (minerals, vitamins amino acids and/or fatty acids) [10,11]. Halophytes also contain ingredients of functional foods and active principles for medicinal supplements [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%